Fault classification approach for double circuit transmission lines using wavelet transforms. (15th April 2011) - Gayathri, K.; Kumarappan, N.
A new approach is developed to enhance the solution of the problems associated with double circuit transmission lines for the mutual coupling (highly variable in nature) between the two circuits under fault conditions. The algorithm depends on the three-line voltage and the six-line currents of double circuit lines at one end. The threshold values involve fault classification and these are done on the basis of the multiresolution analysis (MRA). The main objective is to classify the fault type and it is tested with different values of internal impedance of the generator and the load models of different source resistance, source inductance in double circuit transmission lines using wavelet transform. The result of application of DWT to the double circuit transmission line with mutual coupling is effective and healthy with short duration of time by using Daubechies 4 and 9.